Biomechanical differences in trampoline jumps from hopping on a floor - Muramatsu, S.; Nezu, T. (2001)
Jumps on a trampoline appear to be different from jumps on a floor, however, it has not been fully investigated how they are different. The purpose of this study was to compare trampoline jumping (TJ) and hopping on a floor (FJ) from biomechanical point of views. Five students aged 20-23 years old performed five consecutive jumps on a trampoline and on the floor with the same subjective intensity. The both jumping motions were filmed and analyzed using a high speed video camera system. EMG of the leg muscles (tibialis anterior, gastrocnemius, vastus lateralis and biceps femoris) during the jumping they were recorded using a telemeter and analyzed by a computer. The take off velocity of the center of gravity for the TJ was approximately twice as high as that of the FJ. In the both TJ and FJ, the peak angular velocity (PAV) of the plantar flexion was greater than that of the knee extension, however the PAV and the range of motion of the ankle and knee joints in the FJ were significantly greater than those of the TJ. The difference in the PAV between the ankle and knee joint for TJ was significantly smaller compared to FJ. Vastus lateralis and the gastrocnemius muscles did not work together for the FJ, however, the muscles synchronized for TJ when taking off. The largest integrated EMG was observed in the vastus lateralis for the FJ, but in the gastrocnemius for the TJ. These results indicate that the planter flexors played more important role in the TJ compared to the FJ.